The Practicality of Local Potential-Based Booklets as Enrichment Materials for the Concept of Biodiversity in High Schools: Kepraktisan Booklet Berbasis Potensi Lokal sebagai Bahan Pengayaan Konsep Keanekaragaman Hayati di SMA - Erna; Mahrudin; Iriyanti, Riya (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2025)
Twenty one century education requires educators to have innovative and creative skills in developing teaching materials to support the achievement of learning objectives. One of the teaching materials that can be developed is a booklet. Booklets include printed teaching materials that have the advantage of not requiring an internet connection in accessing them, presenting colorful content, attractive images or illustrations. Booklet development can contain plant diversity material based on local potential, like Moraceae family. Moraceae plants are often encountered by students in their daily lives. Booklet development involves product feasibility testing, one of which is validity. This study aims to describe the validity of the developed booklet. This development research (R&D) uses the Plomp model which consists of 5 stages. The booklet validity test results obtained a score of 91.40% (very valid). The test results show that the developed booklet is ready to be implemented as an enrichment material for the concept of biodiversity because it has fulfilled 12 aspects of the validity of teaching materials and has been revised so that it has good quality. The material in the booklet is designed to adjust the competence of students, the demands of the curriculum, and based on scientific principles.